Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acs.chemrev.1c00694
|View full text |Cite
|
Sign up to set email alerts
|

Metal Complexes of Porphyrinoids Containing Nonpyrrolic Heterocycles

Abstract: The replacement of one or more pyrrolic building block(s) of a porphyrin by a nonpyrrolic heterocycle leads to the formation of so-called pyrrole-modified porphyrins (PMPs), porphyrinoids of broad structural variability. The wide range of coordination environments (type, number, charge, and architecture of the donor atoms) that the pyrrole-modified frameworks provide to the central metal ions, the frequent presence of donor atoms at their periphery, and their often observed nonplanarity or conformational flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 512 publications
2
25
0
Order By: Relevance
“…The formation of 7 appeared to be kinetically irreversible, which was empirically supported by an unsuccessful attempt to transform 7 into 8a upon exposure to the optimized reaction conditions using alkyne 6 and Py (Figure a; more detailed data are summarized in Supporting Information Section 3). On the other hand, using the more electron-rich pyridines Py and Py favors the formation of pyridine adducts INT-III′ , III from dinitrilium intermediate INT-II , which likely suppresses the undesired formation of ddc dication 7 . Py, which bears three methoxy substituents, is better suited to temporarily protect the intermediate as pyridine adducts and more easily accepts the addition of alkyne 6 from INT-III′ to INT-Alk , which is consistent with the experimental observation that Py outperforms Py and Py in terms of the yield of TEQ 8a .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of 7 appeared to be kinetically irreversible, which was empirically supported by an unsuccessful attempt to transform 7 into 8a upon exposure to the optimized reaction conditions using alkyne 6 and Py (Figure a; more detailed data are summarized in Supporting Information Section 3). On the other hand, using the more electron-rich pyridines Py and Py favors the formation of pyridine adducts INT-III′ , III from dinitrilium intermediate INT-II , which likely suppresses the undesired formation of ddc dication 7 . Py, which bears three methoxy substituents, is better suited to temporarily protect the intermediate as pyridine adducts and more easily accepts the addition of alkyne 6 from INT-III′ to INT-Alk , which is consistent with the experimental observation that Py outperforms Py and Py in terms of the yield of TEQ 8a .…”
Section: Results and Discussionmentioning
confidence: 99%
“…On the other hand, using the more electron-rich pyridines Py and Py favors the formation of pyridine adducts INT-III′ , III from dinitrilium intermediate INT-II , which likely suppresses the undesired formation of ddc dication 7 . Py, which bears three methoxy substituents, is better suited to temporarily protect the intermediate as pyridine adducts and more easily accepts the addition of alkyne 6 from INT-III′ to INT-Alk , which is consistent with the experimental observation that Py outperforms Py and Py in terms of the yield of TEQ 8a .…”
Section: Results and Discussionmentioning
confidence: 99%
“…89 Porphodilactone is a porphyrinoid product in which two 3,4-pyrrolic CQC bonds are replaced by two lactone moieties with cis-or trans-carbonyl groups. [159][160][161] To date, Zhang and co-workers have reported that the resulting configurational difference may be used to tune photophysical properties, 162 affect the self-assembly morphology, 163 modulate the extent of aromaticity, 164 and modify the efficacy of photon upconversion. 165 In the case of Zhang and co-worker's porphodilactone, regioisomerism modulated the T 1 energy state of cis/trans-F 20 TPPDL, in loose analogy to ChI b, d, and f (Fig.…”
Section: Regioisomerism Effectsmentioning
confidence: 99%
“…Porphyrin, a nitrogen-functionalized pseudo-D4h-symmetric 18π aromatic macrocycle, is arguably one of the most important naturally occurring small cyclic molecules, whose metal complexes enable a myriad of enzymatic chemical transformations as essential cofactors and serve as key signalling and transportation substances in a vast array of living organisms 1,2 . Thus, porphyrins have inspired decades of intense research on their structural modification, which has led to a variety of porphyrinoids and their metal complexes in order to explore new molecular functions [3][4][5][6][7] . Among the related macrocycles that feature four inwardly oriented nitrogen atoms, structures are usually characterized according to the number of protonated and positively charged nitrogen atoms and the overall architecture (Fig.…”
Section: Introductionmentioning
confidence: 99%